Familial early onset of type-2 diabetes mellitus and its complications - Jali, Mallikarjun V. (Medknow Publications & Media Pvt Ltd, 2009)
BACKGROUND: Globally, the prevalence of chronic, non-communicable diseases is increasing at an alarming rate. Furthermore, approximately 197 million people worldwide have impaired glucose tolerance. Consequently, diabetes is rapidly emerging as a global health problem that threatens to assume a pandemic level by 2030. In Indian population, genetic predisposition to trigger diabetes at an early age as compared to western counterpart has been focused very much. AIM: To gain further insight into the positive correlation between the diabetes and family history was the objective of this study. MATERIALS AND METHODS: Patients attending the Diabetes Centre, K.L.E.S Dr. Prabhakar. Kore Hospital and Medical Research Centre; J. N. Medical College; KLE University Belgaum, Karnataka- India, were recruited, diagnosed and analyzed as per WHO criteria. RESULTS: The prevalence of diabetes was higher among patients with diabetic mother (25.6%) compared to patients with diabetic father (21.2%) and there was early onset of type -2 diabetes among patients having both parents with diabetic when compared to other patients. CONCLUSION: Based on the present observation, it would be appropriate to emphasize again that a strong family history for diabetes, would signal at an early age, the onset of diabetes perhaps with its complications.